Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1152/ajpregu.90731.2008
|View full text |Cite
|
Sign up to set email alerts
|

Salt-resistant blood pressure and salt-sensitive renal autoregulation in chronic streptozotocin diabetes

Abstract: Hyperfiltration occurs in early type 1 diabetes mellitus in both rats and humans. It results from afferent vasodilation and thus may impair stabilization of glomerular capillary pressure by autoregulation. It is inversely related to dietary salt intake, the "salt paradox." Restoration of normal glomerular filtration rate (GFR) involves increased preglomerular resistance, probably mediated by tubuloglomerular feedback (TGF). To begin to test whether the salt paradox has pathogenic significance, we compared inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 97 publications
5
28
2
Order By: Relevance
“…Salt-sensitive hypertension is well known in some humans and other animals [22], and a high incidence of salt sensitivity of BP has been suggested in the evolution of diabetes mellitus [23], although this too is not a universal finding [24]. Therefore, we first showed that increasing salt intake from 1% to 3% by weight of food eaten did not affect BP in intact rats or in poorly controlled type 1 diabetes [16]. The salt paradox was confirmed, but since no pathological changes were seen, that study did not test whether increasing salt intake affected susceptibility to nephropathy in type 1 diabetes.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Salt-sensitive hypertension is well known in some humans and other animals [22], and a high incidence of salt sensitivity of BP has been suggested in the evolution of diabetes mellitus [23], although this too is not a universal finding [24]. Therefore, we first showed that increasing salt intake from 1% to 3% by weight of food eaten did not affect BP in intact rats or in poorly controlled type 1 diabetes [16]. The salt paradox was confirmed, but since no pathological changes were seen, that study did not test whether increasing salt intake affected susceptibility to nephropathy in type 1 diabetes.…”
Section: Introductionmentioning
confidence: 83%
“…Data were acquired at 1,000 Hz in 10 s bursts every 2 min. Systolic BP is reported in order to maintain consistency with previous studies in the literature [7,14,16] and because it is more closely correlated with organ damage than mean or diastolic BP [10]. Body weight and blood glucose were measured twice weekly in all animals; blood samples were acquired from the tail of conscious, unrestrained rats.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations